Arahan revitalisasi Kawasan Kota Lama Mentok Kabupaten Bangka Barat sebagai kota pusaka - Yusi Febriani Yusi; Janthy Trilusianthy Hidayat; Rifdah Dhiyaul Auliyah (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Revitalization Guidelines for the Old Town of Mentok, West Bangka Regency, as a Heritage City. West Bangka Regency has been designated as a heritage city due to its long history, particularly in the Old Town of Mentok. However, the area is poorly maintained and lacks clear zoning. This study aims to analyze the establishment of revitalization zones, the aspects influencing revitalization, and formulate revitalization guidelines for the area. The methods used include qualitative descriptive analysis, delineation analysis, and the Delphi method. The analysis results indicate that the Old Town of Mentok consists of three clusters: the European Cluster, the Malay Cluster, and the Chinese Cluster. The revitalization zones are divided into core zones, supporting zones, and buffer zones. Aspects influencing revitalization include physical aspects (environmental quality, heritage quality, infrastructure, facilities, and cluster circulation) as well as socio-cultural and policy aspects (community activities, public awareness and involvement in heritage preservation, cultural values, local community engagement, government roles, ownership status, and natural disasters). The revitalization guidelines based on physical aspects involve maintaining land use functions in the core zone while allowing changes in the supporting and buffer zones. Meanwhile, socio-cultural and policy-based guidelines include raising public awareness about heritage value in the supporting and buffer zones and implementing policies for the protection, development, and utilization of heritage in all zones. Keywords: Cluster, Old Town, Delphi Method, Revitalization Area, Zoning Area